Virtual Tour Objek Wisata Kabupaten Siak Berbasis Website - Ade Syefira Rizky; Andri Nofiar Am; Ade Kurniawan (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
The website-based Virtual Tour of Siak Regency Tourist Attractions is an innovation that uses 306 degree image displays. This Virtual Tour was created using PHP, Javascript, and MySQL, with Bootstrap v5.0 and Bootstrap v3.0 displays via HTML and CSS. The system is designed in the form of a virtual tour to display the location points of the distribution of tourist attractions in Siak Regency. Luther's method was used to complete the research carried out. This research succeeded in creating a virtual tour that can be accessed via a website, providing information on the distribution of tourist attraction locations with the aim of making it easier for the public, especially newcomers, to obtain information regarding tourist attractions in Siak Regency. With this virtual tour, it is hoped that it will make it easier for the public, especially newcomers, to obtain information about tourist attractions in Siak Regency. The results of the average user response reached 91% stated that the website was very good.